Lack of adoption of electronic Medical Records Systems in developing countries. A case study of Zimbabwe - Mhembere, Taurai Brian (Department of Information Systems, 2020)
This study explored the phenomenon of electronic medical records systems in Zimbabwean primary healthcare institutions. The goal of the study was to investigate the lack of adoption of electronic medical records systems by primary healthcare institutions in developing countries using an interpretative case study approach focusing on the Zimbabwean context. Despite the positive benefits that are associated with EMRs, developing countries have been reluctant in implementing this technology within their primary healthcare institutions. A number of studies have been conducted on EMR systems but only a few have investigated the reasons for the limited use of EMR technology in developing countries particularly within the Zimbabwean context. This study primarily adopted a case study approach and was qualitative in nature. The study made use of in-depth interviews to obtain its data, and purposive sampling method was used to identify participants for the study. The study made use of a sample size of fourteen respondents who were identified based on their knowledge and could assist explore this particular topic relevant to the research. The targeted population for this research were key staff members privy to patients’ medical records management within the primary healthcare facilities. The data collected was analysed using thematic analysis soon after the transcription process. The results of the study show that EMRs technology in Zimbabwe has been implemented on a limited scale within its public hospitals. The technology is being used mostly in HIV/AIDS management or in particular departments. The study reveals that although healthcare institutions in Zimbabwe have adopted EMRs technology, most of the information is still being archived on the paper based system. The findings of the study show that Zimbabwe hasn’t adopted EMRs due to challenges such as lack of proper infrastructures, resistance in the use of EMRs, remoteness, shortages in skilled labour and concerns of confidentiality and privacy. Furthermore, the study shows that though the application of the EMR system is limited in Zimbabwean hospitals, the study found that its benefits have been noticeable. EMR technology has made it easy to access information, averted redundant expenditure and has made time improvements. However, the study revealed that EMR systems come with their own shortcomings such as lack of access to patient documents due to network faults and the need for familiarity with computer systems.